2015
DOI: 10.1080/0376835x.2015.1063985
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between BRIC foreign direct investment and SADC export performance?

Abstract: and South Africa) group of countries have agreed to strengthen their economic ties, thus paving the way for enhanced trade and investment performance. South Africa's strategic value in BRICS is that it is a gateway to the opportunity-rich SADC (Southern African Development 2 Community). By using South Africa as a production hub for exports to the surrounding region, foreign investors would have ready access to neighbouring markets. This article addresses the question of whether, and in what ways, FDI (foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Although the trade flows of BRICS members has drawn some attention from researchers-Yavuz Cakir and Kabundi (2013), Yin (2014), Izotov (2007), Nayyar Rahman (2016), Bezuidenhout and Claassen (2013), Clus-Rossouw et al (2015) Caporale et al (2015, and Fung et al (2015)-we do not find a study that analyzes the similarity in trade integration patterns of BRICS members using a gravity model. This study will fill the gap.…”
Section: Introductionmentioning
confidence: 72%
“…Although the trade flows of BRICS members has drawn some attention from researchers-Yavuz Cakir and Kabundi (2013), Yin (2014), Izotov (2007), Nayyar Rahman (2016), Bezuidenhout and Claassen (2013), Clus-Rossouw et al (2015) Caporale et al (2015, and Fung et al (2015)-we do not find a study that analyzes the similarity in trade integration patterns of BRICS members using a gravity model. This study will fill the gap.…”
Section: Introductionmentioning
confidence: 72%
“…A majority of scholars, however, claim that FDI has a positive impact on economy (Zghidi et al, 2016). They emphasize that FDI accelerates the host countries' economic growth (le Clus-Rossouw et al, 2015). Several studies find that FDI contributed to the economic growth in many countries such as Slovakia (Szkorupová, 2014), Malaysia (Alzaidy et al, 2017), Pakistan (Ali and Hussain, 2017), Vietnam (Nguyen, 2020), Cambodia (Sokang, 2018), Albania (Boriçi and Osmani, 2015), Bosnia and Herzegovina (Susic et al, 2017), Nigeria (Udeh andOdo, 2017), andGhana (MENSAH, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various empirical studies have shown the potential reverse causal link between trade and investment. Le Clus-Rossouw et al (2015) contend that increasing FDI from the BRIC countries (Brazil, Russia, India, and China) to South Africa successfully resulted in an increase of export performance from Africa to the BRIC. Another empirical study by Liargovas and Skandalis (2012) also agrees with the positive correlation between trade openness to FDI inflows in 36 developing countries.…”
Section: Improve Cooperation Between Bkpm and Motmentioning
confidence: 99%